Potential Therapeutic Targets for Combination Antibody Therapy against Pseudomonas aeruginosa Infections - Luke L. Proctor; Whitney L. Ward; Conner S. Roggy; Alexandra G. Koontz; Katie M. Clark; Alyssa P. Quinn; Meredith Schroeder; Amanda E. Brooks; James M. Small; Francina D. Towne; Benjamin D. Brooks (MDPI AG, 2021)
Despite advances in antimicrobial therapy and even the advent of some effective vaccines, Pseudomonas aeruginosa (P. aeruginosa) remains a significant cause of infectious disease, primarily due to antibiotic resistance. Although P. aeruginosa is commonly treatable with readily available therapeutics, these therapies are not always efficacious, particularly for certain classes of patients (e.g., cystic fibrosis (CF)) and for drug-resistant strains. Multi-drug resistant P. aeruginosa infections are listed on both the CDC's and WHO's list of serious worldwide threats. This increasing emergence of drug resistance and prevalence of P. aeruginosa highlights the need to identify new therapeutic strategies. Combinations of monoclonal antibodies against different targets and epitopes have demonstrated synergistic efficacy with each other as well as in combination with antimicrobial agents typically used to treat these infections. Such a strategy has reduced the ability of infectious agents to develop resistance. This manuscript details the development of potential therapeutic targets for polyclonal antibody therapies to combat the emergence of multidrug-resistant P. aeruginosa infections. In particular, potential drug targets for combinational immunotherapy against P. aeruginosa are identified to combat current and future drug resistance.